Program Kerja Dinas Perpustakaan Dan Arsip Daerah Kabupaten Padang Lawas Utara Dalam Pembinaan Perpustakaan Sekolah - Hasibuan, Armen Natohong; Monang, Sori; Jamil, Khairul (Jurnal Manajemen Akuntansi (JUMSI), 2024)
According to the Indonesian National Standard, a school library is a library located in a formal education unit in primary and secondary education which is an integral part of the school's activities and is a learning resource center to support the achievement of the school's educational goals. From the above understanding until now, the existence of the school library has not functioned as expected. because in reality the library is still nothing more than a place to store books. Because school students are less interested in going to the library to find information. One of the efforts or actions to develop the school library is to carry out coaching activities. This study uses qualitative research with the type of research that is descriptive research. The purpose of this study is first, to find out the work program of the Regional Library and Archives Office of North Padang Lawas Regency in fostering school libraries. Second, to find out the obstacles faced by the Regional Library and Archives Office of North Padang Lawas Regency in carrying out work programs on school library development. The findings in this study are first, the development of library materials processing, the forms of library materials processing i.i. carried out by the iDinas iLibrary and iArchives in the form of checking library materials, the cataloging of library materials, iphysical completion, idevelopment of work staff in the school library. Second, the obstacle faced in fostering school libraries is the lack of human resource competence.